OPTIMALISASI PERAN TUTOR INTI SEBAGAI TIM TEACHING DAN PEER TUTORING - Erman Syamsuddin (JIV-Jurnal Ilmiah Visi, 2008)
Non-formal Education (NFE) is still facing insufficient number and quality of tutors and thiese become serious obstacles in implementing NFE programs. Meanwhile a continous quality improvement of various NFE activities is required to meet the societyâ€™s needs. This article discusses the necessities of developing master tutors based on philosophical, legal, and empirical studies.